The duration of economic expansions and recessions: more than duration dependence - Castro, Vítor (2008)
One widespread idea in the business cycles literature is taht the older is an expansion or contraction, the more likely it is to end. This paper tries to provide further empirical support for this idea of positive duration dependence and, at the same time, control for the effects of other factors like leading indicators, the duration of the previous phase, investment, price of oil and external influences on the duration of expansions and contractions. This study employs a discrete-time duration model to analyse the impact of those variables on the likelihood of an expansion and contraction ending for a group of industrial countries over the last fifty years. The evidence provided in this paper suggests that the duration of expansions and contractions is not only dependent on their actual age: the duration of expansions is also positively dependent on the behaviour of the variables in the OECD composite leading indicator and on private investment, and negatively affected by the price of oil and by the occurence of a peak in the US business cycle; the duration of a contraction is negatively affected by its actual age and by the duration of the previous expansion.